2016
DOI: 10.1073/pnas.1607152113
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SAT1 engages polyamine metabolism with p53-mediated ferroptotic responses

Abstract: Although p53-mediated cell-cycle arrest, senescence, and apoptosis remain critical barriers to cancer development, the emerging role of p53 in cell metabolism, oxidative responses, and ferroptotic cell death has been a topic of great interest. Nevertheless, it is unclear how p53 orchestrates its activities in multiple metabolic pathways into tumor suppressive effects. Here, we identified the SAT1 (spermidine/spermine N 1 -acetyltransferase 1) gene as a transcription target of p53. SAT1 is a rate-limiting enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
442
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(504 citation statements)
references
References 41 publications
11
442
3
4
Order By: Relevance
“…25,26,53,63 One such study suggested that α-TOH inhibits ferroptosis by LO inhibition. 63 The basis for this assertion was that tocotrienols were demonstrably more effective inhibitors of ferroptosis than tocopherols, and tocotrienols were predicted to bind more strongly to 15-LOX-1 than tocopherols owing to the three unsaturations in their lipophilic side chains.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,53,63 One such study suggested that α-TOH inhibits ferroptosis by LO inhibition. 63 The basis for this assertion was that tocotrienols were demonstrably more effective inhibitors of ferroptosis than tocopherols, and tocotrienols were predicted to bind more strongly to 15-LOX-1 than tocopherols owing to the three unsaturations in their lipophilic side chains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selenium supplementation promotes ferroptosis resistance, while selenium depletion promotes ferroptosis sensitivity, presumably by modulating GPX4 abundance and activity (Cardoso et al, 2017). A number of other genes have been implicated as modulators of sensitivity to ferroptosis or markers of ferroptosis in diverse contexts: SAT1 , which lies downstream of p53 (Ou et al, 2016) is involved in polyamine metabolism; kiss of death (KOD) in Arabidopsis (Distefano et al, 2017) and FANCD2 in bone marrow stromal cells are induced during ferroptosis (Song et al, 2016); TTC35 , CS , ATP5G3 , and RPL8 are involved in diverse processes in human cancer cells and suppress erastin-induced ferroptosis upon knockdown (Dixon et al, 2012). …”
Section: The Biochemical Control Of Ferroptosismentioning
confidence: 99%
“…SAT1 is a rate-limiting enzyme in polyamine catabolism critically involved in the conversion of spermidine and spermine back to putrescine. Surprisingly, activation of SAT1 expression induces lipid peroxidation and sensitizes cells to undergo ferroptosis upon ROS-induced stress [78]. …”
Section: Ferroptosis Induced By Rosmentioning
confidence: 99%